On Quantum Transition in Cryptography through the Lens of Bibliometrics - Terekhov, A. I. (Automatic documentation and mathematical linguistics, 2025)
Cryptography, which has a history going back many centuries, is currently experiencing a transition from the classical paradigm to a quantum one. Using bibliometrics, the dynamics of development and the ratio between three branches of cryptography—classical, postquantum, and quantum—in the period 1990–2020 are considered; the restructuring of the crypto-sphere in favor of the quantum paradigm since 2015 is noted. The world leaders in quantum cryptography research are industrialized countries, including the G7 group and China, and at the institutional level, leading universities, academic organizations, technology institutes, as well as large corporations, especially from Japan and the United States, and military research institutions, especially from the United States and China. The features of the quantum-cryptographic ecosystems of several countries are identified. It is shown that, in Russia, research is concentrated in the academic sector, universities and specialized organizations—the Academy of Cryptography of the Russian Federation, the Russian Quantum Center. By contrast with leading countries, the contribution of domestic corporations and small businesses is still limited. Geopolitical aspects of creating quantum-cryptographic security have been discussed. The Web of Science Core Collection database is used as a source for bibliometric analysis.